2007
DOI: 10.1016/j.coph.2007.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Accumbens dopamine-acetylcholine balance in approach and avoidance

Abstract: SummaryUnderstanding systems for approach and avoidance is basic for behavioral neuroscience. Research on the neural organization and functions of the dorsal striatum in movement disorders, such as Huntington's and Parkinson's Disease, can inform the study of the nucleus accumbens (NAc) in motivational disorders, such as addiction and depression. We propose opposing roles for dopamine (DA) and acetylcholine (ACh) in the NAc in the control of GABA output systems for approach and avoidance. Contrary to DA, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
117
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(124 citation statements)
references
References 81 publications
6
117
1
Order By: Relevance
“…Cholinergic interneurons intrinsic in the nucleus accumbens (NAc) are potentially an important target for antidepressant treatments (Chau et al, 2001;Hoebel et al, 2007;Rada et al, 1993Rada et al, , 2006. These neurons are the sole source of local acetylcholine (ACh) in the NAc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cholinergic interneurons intrinsic in the nucleus accumbens (NAc) are potentially an important target for antidepressant treatments (Chau et al, 2001;Hoebel et al, 2007;Rada et al, 1993Rada et al, , 2006. These neurons are the sole source of local acetylcholine (ACh) in the NAc.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous data suggest that ACh opposes the action of dopamine (DA) in the control of the accumbens g-aminobutyric acid output systems for approach and avoidance behavior (Hoebel et al, 2007). We found that ACh release in the NAc (especially in the posterior medial NAc, ie, the shell) is a correlate or a cause of meal satiation (Avena et al, 2006;Mark et al, 1992), conditioned taste avoidance (Mark et al, 1995), escape from aversive brain stimulation , and anxiety during the state of drug withdrawal (Rada et al, 1991 and sugar withdrawal (Avena et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Dopamine and acetylcholine (ACh) functions are well known in the BIS and BAS related structures. The nucleus accumbens is involved in general incentive motivation for approach behavior depending on ACh and dopamine levels (Hoebel et al 2007). It has been shown previously that simvastatin application alters dopaminergic and cholinergic levels in the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, neural systems responsible for generating approach behavior must be countered by signals that suppress approach behavior under contexts where approach is dangerous or maladaptive (Hoebel et al 2007). The nucleus accumbens (NAc) is acutely involved in food intake and goal-directed, approach behavior.…”
mentioning
confidence: 99%